Assessing the Economic Feasibility of Assuring Nutritionally Adequate Diets for Vulnerable Populations in Uttar Pradesh, India: Findings from a "Cost of the Diet" Analysis. Issue 12 (13th November 2020) - Kachwaha, Shivani; Nguyen, Phuong Hong; DeFreese, Michelle; Avula, Rasmi; Cyriac, Shruthi; Girard, Amy; Menon, Purnima
ABSTRACT: Background: Healthy diets can help reduce undernutrition, morbidity, and mortality. However, evidence on the accessibility and affordability of recommended diets is limited, particularly in poor-resource settings including India. Objectives: This study examined: 1 ) the minimum cost of different types of household diets; 2 ) how economic constraints can prevent households from accessing a nutritious diet; and 3 ) how home production and social protection can improve access to nutritious diets. Methods: We conducted 24 market and 125 household surveys in Uttar Pradesh, India, to obtain food prices and consumption patterns. Cost of Diet, a linear programming software, was used to assess the minimum cost of different diets, estimate affordability of nutritious diets, and model scenarios of home production and social protection interventions to improve affordability. Results: The minimum-cost nutritious diet that met all recommended nutrient requirements [904 US dollars (US$)/y] was over twice as expensive as the diet that only met energy requirements (US$393/y). The nutritious diet was unaffordable for 75% of households given current income levels, consumption patterns, and food prices. Household income and dietary preferences, rather than food availability, were the key barriers to obtain nutritious diets. Home production had potential to reduce the cost of nutritious diets by 35%, subsidized grains by 19%, and supplementary food by 10%. The poorest households could only afford recommended nutritious diets with access to multiple interventions. Conclusions: Practical, habitual, diet-related behavior change communication to middle- and high-income households and additional social protection for poorer households could enable individuals to achieve optimal nutrient intakes.